Ustrój i prawo starożytnego Rzymu w świetle krakowskich wydań De magistratibus et sacerdotiis, praeterea de diversis legibus Romanorum Giulia Pomponia Leto - Dyjakowska, Marzena (PRAWO i WIĘŹ, 2025)
The article is devoted to the political and legal system of ancient Rome, especially during the Republic, in the light of the treatise written by the Renaissance scholar Pomponio Leto. The treatise was well-received in sixteenth-century Poland, as evidenced by the four Krakow editions. The author of the treaty (1428–1497) was an Italian humanist, professor of eloquence in Rome, and founder of the Academia Romana, where members discussed various questions of ancient history and literature. His treatise De Romanorum magistratibus, sacerdotiis, iurisperitis et legibus is considered by many scholars to be a „by-product” of work related to the publication of texts by Roman historians, commenting on the works of Virgil, and especially work on the texts of Varro. The author of the paper aims also to demonstrate the influence of sources of Roman law, particularly fragments of Justinian's Digests, on the content of the treatise, often overlooked by most researchers.